Activities of the Sex-lethal protein in RNA binding and protein:protein interactions. - Samuels, M (1998)
The Drosophila sex determination gene Sex-lethal (Sxl) controls its own expression, and the expression of downstream target genes such as transformer , by regulating pre-mRNA splicing and mRNA translation. Sxl codes an RNA-binding protein that consists of an N-terminus of approximately 100 amino acids, two 90 amino acid RRM domains, R1 and R2, and an 80 amino acid C-terminus. In the studies reported here we have examined the functional properties of the different Sxl protein domains in RNA binding and in protein:protein interactions. The two RRM domains are responsible for RNA binding. Specificity in the recognition of target RNAs requires both RRM domains, and proteins which consist of the single domains or duplicated domains have anomalous RNA recognition properties. Moreover, the length of the linker between domains can affect RNA recognition properties. Our results indicate that the two RRM domains mediate Sxl:Sxl protein interactions, and that these interactions probably occur both in cis and trans. We speculate that cis interactions between R1 and R2 play a role in RNA recognition by the Sxl protein, while trans interactions stabilize complex formation on target RNAs that contain two or more closely spaced binding sites. Finally, we show that the interaction of Sxl with the snRNP protein Snf is mediated by the R1 RRM domain.